NILAI TAMBAH DAN PEMASARAN PRODUK OLAHAN TAPE PADA AGROINDUSTRI RAJA TAPE 31 DI KABUPATEN BONDOWOSO - Marhamah, Marhamah; Aji, Joni Murti Mulyo (Mimbar Agribisnis : Jurnal Pemikiran Masyarakat Ilmiah Berwawasan Agribisnis, 2023)
Raja Tape 31 agro-industry is a tape-processed agro-industry located in Nangkaan Village, Bondowoso Regency. It has a problem with decreasing sales volume due to the Covid-19 pandemic, while the price of cassava and its raw materials are getting expensive and difficult to obtain. This research aims to identify sales volume, added value, channels and marketing margins. The sampling method is purposive sampling method. Methods of data analysis using descriptive statistics, Hayami added value table, marketing channels and margins analysis. The results show that the sales volume of Raja Tape 31 Agroindustry experienced sales fluctuations and sales of dodol tape and pia tape decreased by 25-30%. The added value of processed tape products into dodol tape and pia tape at Raja Tape 31 Agroindustry provides positive added value where VA > 0. The added value of dodol tape is Rp.6,471.75/kg of raw tape and glutinous rice flour with a value added ratio of 18.34 %. Meanwhile, the added value of pia tape is Rp.46,202.61/kg of tape raw materials and wheat flour with an added value ratio of 40.62%. There are two marketing channel patterns for dodol tape and pia tape products in the Raja Tape 31 Agro-industry in Bondowoso Regency, namely: a. Marketing channel I (Level zero): Producers – Consumers. b. Marketing channel II (Level one): Producers - Retailers - Consumers. (4) The margin for marketing channel I for dodol tape is 0 and for marketing channel level II for dodol tape is Rp. 2,000 with distribution for a 45.00% profit share and 9.00% costs. The margin for marketing channel I pia tape is 0 and marketing channel II is Rp.3000 with a profit share distribution of 63.33% and costs 12.67%.